Thermostable alkaline protease activity from Aspergillus flavus DUCC- K225 and its compatibility to local detergents - A N S Rini; Isworo Rukmini; S Pujiyanto (Microbiology Indonesia, 2021)
Protease is the most important enzyme in many industries, including detergent. Aspergillus flavus DUCC-K225 is a thermotolerant indigenous molds isolated from Madura island which is potential in producing thermostable alkaline protease enzymes. The enzyme produced by submerged culture on modified Czapeks Dox liquid medium containing glucose as carbon source and 1% of casein. The aims of this study were to determine the activity and stability of thermostable alkaline protease produced by A. flavus DUCC-K225 at various temperatures, also the compatibility to 5 local detergents. Research were done using CRD, with temperature variation for protease activity as treatment. The results showed that the optimum activity of thermostable alkaline proteases was 214.503 U/mL, with retained activities up to 78% in 60 minutes at 55Â°C. The alkaline thermostable protease compatible with 5 local detergents tested, with the retained activity varied 55.8%-95.22% at 29oC and 62.36%-97.7% at 55oC. The compatibility to detergent confirmed by blood stained cleansed. The higher the protease activity, the higher the blood stain solubility. Key words: Alkaline protease, thermostable, A. flavus DUCC-K225, compatibility, detergent